2007
DOI: 10.1038/sj.eye.6702838
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmological problems associated with preterm birth

Abstract: As survival of preterm infants improves, the long-term care of consequent ophthalmic problems is an expanding field. Preterm birth can inflict a host of challenges on the developing ocular system, resulting in the visual manifestations of varied significance and pathological scope. The ophthalmic condition most commonly associated with preterm birth is retinopathy of prematurity, which has the potential to result in devastating vision loss. However, the visual compromise from increased incidence of refractive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(102 citation statements)
references
References 68 publications
3
96
1
2
Order By: Relevance
“…The development of medicine has made it possible to rescue children with low birth weight and severe complications resulting from prematurity. In premature infants, numerous health complications are diagnosed: retinopathy, hearing impairment, early brain injury with accompanying hypoxic events and ischemia [4,23,27,30,31]. They can adversely affect their development, including the balance system.…”
Section: Introductionmentioning
confidence: 99%
“…The development of medicine has made it possible to rescue children with low birth weight and severe complications resulting from prematurity. In premature infants, numerous health complications are diagnosed: retinopathy, hearing impairment, early brain injury with accompanying hypoxic events and ischemia [4,23,27,30,31]. They can adversely affect their development, including the balance system.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent hypoxia in the peripheral retina then produces proliferation of blood vessels in the eye of the premature infant (Fleck and McIntosh, 2008). Children with ROP often display abnormal eye movements and crossed eyes, suggesting that developing periocular tissues are also sensitive to variations in oxygen tension (O'Connor et al, 2007). Also important to this study, a strong correlation has been found between strabismus, anisotropia, amblyopia, and microphthalmia among newborns and maternal smoking during pregnancy (Hakim RB, 1992;Lempert, 2005;Ponsonby AL, 2007;Stone RA, 2006).…”
Section: Responses To Hypoxiamentioning
confidence: 83%
“…It is well known that ocular structures are continuing to develop and grow even after birth (22). No doubt that children born prematurely, even without clinically significant complications, have an increased incidence of unfavourable ophthalmic outcomes.…”
Section: Discussionmentioning
confidence: 99%